How operators make use of wide-choice adaptable automation: observations from a series of experimental studies. (4th March 2018) - Sauer, Juergen; Chavaillaz, Alain
ABSTRACT: The present paper is concerned with the design of adaptable automation. It analyses the aggregated data from five experiments ( N = 154) to examine which automation levels operators prefer, how often they switch between them, and whether performance is associated with frequent switching or the automation levels being used. Using wide-choice adaptable automation (i.e. up to six levels were offered), the experiments were conducted using a PC-based simulation of a complex work environment. The results showed that about 95% of operators had a clearly preferred automation level, which they used for more than 50% of the time. They strongly preferred intermediate automation levels over levels at the higher and lower ends of the scale. Most operators switched rarely between levels and when they did, they usually made small adjustment rather than large changes. Several implications for the design of adaptable automation were derived from the empirical data.